The effects of a 6-hour ultra-endurance run on postexercise parasympathetic reactivation responses - Fornasiero, A.; Zignoli, A.; Pellegrini, B.; Schena, F.; Doucende, G.; Mourot, L. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Alterations in cardiac autonomic control reflecting depressed parasympathetic activity have been previously reported after ultra-endurance events at rest and during dynamic tasks assessing cardiac autonomic responsiveness. This study investigated the impact of a 6-hour ultra-endurance run on parasympathetic reactivation indices, using an exercise-recovery transition approach. METHODS: Nine trained runners (VO2max 67±12 mL/kg/min) completed a 6-hour run (EXP) whilst other six runners (VO2max 66±10 mL/kg/min) served as a control (CON). Before (PRE) and after the run/control period (POST) participants completed standard cardiac autonomic activity assessments. Postexercise parasympathetic reactivation was assessed by means of heart rate recovery (HRR) and vagal-related time-domain HRV indices. RESULTS: HR was increased at rest (P<0.001, ES=3.53), during exercise (P<0.05, ES=0.38) and recovery (all P<0.001, ES from 0.91 to 1.46) at POST in EXP and not in CON (all P>0.05). At POST vagal-related HRV indices were significantly decreased at rest (P<0.001, ES from -2.38 to -3.54) and during postexercise recovery (all P<0.001, ES from -0.97 to -1.58) only in EXP. HRR at 30 and 60 s were markedly reduced at POST in EXP both when expressed in bpm and normalized for the exercising HR (all P<0.001, ES from -1.21 to -1.74). CONCLUSIONS: A 6-hour run markedly impacted upon postexercise parasympathetic reactivation responses causing a decrease in HRR and HRV recovery indices. For the first time, this study attested blunted postexercise parasympathetic reactivation responses following an acute bout of ultra-endurance exercise.